Solid Phase Extraction and Graphite Furnace Atomic Absorption Spectrometry for the Determination of Heavy Metal Ions - Zhu, Liya; Li, Kaizhong; Zhou, Shiping; Hu, Qiufen; Yang, Guangyu; Huang, Zhangjie; Chen, Jing (Asian Journal of Chemistry, 2010)
A solid phase extraction method was developed for the preconcentration and separation of trace amounts of chromium, nickel, silver, cobalt, copper, cadmium and lead from environmental samples by complexation with 2-(2-quinolinylazo)- resorcin (QAR) followed by adsorption onto Diaion SP-850 solid phase extraction column. 1.0 mol L-1 HNO3 was used as eluent. The recoveries of analytes at pH 8.0 with 800 mg of resin were more than 95 % without interference from alkaline, earth alkaline and some metal ions. The detection limits by three sigma for analyte ions were 0.32 μg L-1 for Cr(III), 0.21 μg L-1 for Ni(II), 0.14 μg L-1 for Ag(I), 0.36 μg L-1 for Co(II), 0.18 μg L-1 for Cu(II), 0.25 μg L-1 for Cd(II) and 0.30 μg L-1 for Pb(II). The validation of the procedure was performed by the analysis of the certified standard reference materials and the presented procedure was applied to the determination of analytes in biological, water and soil samples with good results (recoveries more than 95 % and RSD % lower than 3.5 %).